2012
DOI: 10.1053/j.gastro.2011.10.026
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatase PHLPP1 Regulates Akt2, Promotes Pancreatic Cancer Cell Death, and Inhibits Tumor Formation

Abstract: BACKGROUND & AIMS The kinase Akt mediates resistance of pancreatic cancer (PaCa) cells to death and is constitutively active (phosphorylated) in cancer cells. Whereas the kinases that activate Akt are well characterized, less is known about phosphatases that dephosporylate and thereby inactivate it. We investigated regulation of Akt activity and cell death by the phosphatases PHLPP1 and PHLPP2 in PaCa cells, mouse models of PaCa, and human pancreatic ductal adenocarcinoma (PDAC). METHODS We measured the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
80
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 34 publications
8
80
0
Order By: Relevance
“…In our current study, we demonstrated that the level of PHLPP expression regulates drug sensitivity in colon cancer cells and that downregulation of PHLPP contributes to hypoxiainduced chemoresistance. These findings are consistent with the established role of PHLPP in promoting apoptosis and inhibiting proliferation in various cancer cells (18,20,23,24,39). In summary, we have identified PHLPP as a critical factor in determining drug sensitivity under hypoxic conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our current study, we demonstrated that the level of PHLPP expression regulates drug sensitivity in colon cancer cells and that downregulation of PHLPP contributes to hypoxiainduced chemoresistance. These findings are consistent with the established role of PHLPP in promoting apoptosis and inhibiting proliferation in various cancer cells (18,20,23,24,39). In summary, we have identified PHLPP as a critical factor in determining drug sensitivity under hypoxic conditions.…”
Section: Discussionsupporting
confidence: 90%
“…As a direct regulator of several critical protein kinases, including Akt, protein kinase C (PKC), mitogen-activated protein kinase (MAPK), and MST1, PHLPP plays a critical role in maintaining the balance of signaling and homeostasis in cells (13)(14)(15)(16). Recently, an increasing numbers of studies have revealed that loss of PHLPP expression is highly associated with tumor progression in both human cancers and mouse models, thus further confirming the role of PHLPP as a tumor suppressor (17)(18)(19)(20). Our previous studies have shown that PHLPP is degraded via the ubiquitin-proteasome pathway, and the turnover of PHLPP proteins is mediated by the E3 ubiquitin ligase ␤-TrCP (21).…”
mentioning
confidence: 88%
“…As Ser/Thr protein phosphatases, PHLPP1 and PHLPP2 can directly dephosphorylate AKT to inhibit AKT signaling activity, which promotes apoptosis (15,30,33). Overexpression of PHLPP1 and PHLPP2 in cancer cell lines decreases cell proliferation and tumorigenesis both in vitro and in xenograft models (26,30,(33)(34)(35)(36)(37). In colorectal cancer cells, stable overexpression of PHLPP1 or PHLPP2 blocked the G 2 -M transition or induced G 1 cell-cycle arrest, thus decreasing the rate of cell proliferation (26).…”
Section: Discussionmentioning
confidence: 99%
“…PH domain and Leucine rich repeat protein phosphatases (PHLPP) levels are markedly reduced in human PDAC that have elevated AKT phosphorylation (71). Studies have shown that PHLPP1 and PHLPP2 are able to terminate AKT signaling by directly dephosphorylating and inactivating AKT resulting in great suppression of tumour growth (72,73).…”
Section: Pancreatic Cancermentioning
confidence: 99%